The Analysis of Network Governance in The Investment Development of Free Trade Zone and Free Port (KPBPB) Batam - Ady Muzwardi (Magister Administrasi Publik, 2015)
Large amount of investment is one of income sources for a country. Recently, the investment in Indonesia has not been managed optimally due to, one among others, poor organization system of investment management. This study is aimed at analyzing the network governance within organization system in investment development at Free Trade Zone and Free Port Batam. The research methodology used was Coordination Network Analysis with 5 aspects of study; those are governance structure, service characteristics, operational interaction of partner characteristics, and network characteristic on 3 organizations at the level of province and regency/city. The result of the analysis indicates that coordination between provincial and regency/city organizations is not yet optimally conducted. Horizontal and vertical coordination are not yet optimally established.